Analysis of Changes in Consumer Behavior and Online Shopping Motivations - Marina Marina; Intisari Haryanti (Almana : Jurnal Manajemen dan Bisnis, 2022)
Changes in consumer behavior and online shopping motives are the tendency of consumers to buy goods that are not following economic conditions but only because of certain factors. In online shopping motives, consumers tend to not observe in detail the products they want to buy, some pictures on the internet are not the same as reality. Even consumers are only interested in the price which tends to be cheap without first paying attention to the quality. The objectives of this research are to find out how online consumer behavior changes in the city of Bima and to find out how the motives for shopping online in the city of Bima. The population in this study are consumers who have done online shopping and the number of samples in this study was 100 respondents while the sampling technique in this study was using purposive sampling. The data analysis technique used the t-test (one-sample t-test). Based on the results using a one-sample t-test test that there is a change in consumer behavior online in the city of Bima. Includes cultural factors, social factors, personal factors, and psychological factors. The shopping motives in question are self-gratification, time, and information.